The significance of implementation of life course concept into the theoretic basis of health promotion - Stanisavljević Sanja (Association of Nurses Technicians and Midwives, 2022)
The acceptance of the postulate that people's health is the general interest of human society and also its basic resource for development represents the shift in the focus of the health care system and the society from disease and treatment to health promotion and preservation, healthy lifestyles affirmation and to development of a healthy environment. The promotion of health is becoming the key area for public healthcare actions, and thus a key element of nursing practice. Through the presentation and comparison of the current concept of health promotion based on the bio-psycho-social model and the basic postulates of the Life Course Theory, the author implies the necessity of expanding the existing frames in health promotion theory and the significance of implementation of Life Course Theory into the nursing curriculum, giving at the same time basic guidelines for its practical application within the health promotion activities of the nurses.